Analisis Kebutuhan Media Pembelajaran Berbasis Augmented Reality Materi Indonesiaku Kaya Budaya Di Kelas IV Sekolah Dasar - Rizky Oktavian; Wendri Wiratsiwi (Prodi Pendidikan Guru Sekolah Dasar, 2026)
The use of learning media is still very limited in the practice of implementing learning. Teachers only focus on lectures and assignments. There is no interactive media used in the learning process. This study uses a qualitative research approach with a qualitative descriptive research type. The subjects of this study were 1 fourth grade teacher and 28 students. The data collection methods used were observation, interviews and documentation. The results of observations were carried out by researchers to obtain direct data regarding field conditions in grade IV Elementary School, Learning still uses conventional methods. The learning process is still filled with lectures from a teacher, and assignments are only sourced from 2D printed books. The results of interviews with fourth grade homeroom teachers show that the learning process on the material Indonesia is Rich in Culture still encounters several obstacles, especially in terms of delivering abstract material. The results of the analysis of learning media needs in grade IV Elementary School require learning media that are concrete, visual and interactive. Because it is in accordance with the characteristics of elementary school students who are still in the concrete operational stage. They find it easier to understand material through direct visualization. Augmented reality is a relevant solution because it can present learning objects in interactive and engaging three-dimensional visuals. Therefore, this augmented reality-based learning medium can increase student interest and learning outcomes, engagement, and understanding of the material.